Evaluasi Penggunaan Analgetik Pasca Bedah Apendisitis di Rawat Inap RSUP Fatmawati Jakarta: Analgetic Use Evaluation of Post Apendicitic Surgery Inpatients of Fatmawati Hospital, Jakarta - Agas Kurnia Anugrah; Lusi Agus Setiani; Naufal Muharam Nurdin (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Appendicitis is a disease caused by vermimorphic inflammation caused by blockages in the lining of the appendix, so it is necessary to perform surgery to treat the pain caused postoperatively will give a feeling of discomfort and potential complications, therapy given to control the pain that is analgetic administration. The purpose of this study is to know the pattern of analgetic use, evacuate the pattern of analgetic use and know the effectiveness of analgetic use in patients post-surgical appendicitis at RSUP Fatmawati Jakarta Year 2019 with retrospective methods and univariate statstic test to determine the distribution of patient characteristics and distribution of analytical use then wilcoxon statistical test to know the relationship of analytical use to decrease the degree of pain. The results of the study were based on univariate methods of patients suffering from mild pain as much as (60.0%), moderate pain (40.0%) then after administered analgetic patients who do not feel pain (10,5%) mild pain (88.4%) moderate pain (1,1%), then the results of each analgetic wilcoxon test showed, that the administration of a single analgetik influences the decrease in the degree of nnyeri with the results of P-value for Tramadol, Paracetamol, and Ketorolac 0,005.